Patents 2.0 [software patents]. - Hollaar, Lee A. (IEEE spectrum)
Because the current procedure for securing software patents is laden with problems, a new form of intellectual property should be considered that gives reduced benefits in exchange for speedy protection. A new limited patent is proposed that grants protection from the moment the technology is first used in commerce. The primary purpose of the limited patent is to provide immediate protection for technology that, once on the market, could otherwise be copied by a competitor before regular patent protection could be secured. Protection should last long enough to allow inventors to have immediate protection against knockoffs of a technology even as they try to get broader protection by meeting the more stringent requirements for a conventional patent. This would encourage further innovation because new features could get their own protection.